Rhizobium Inoculation of Cowpea in Brazilian Cerrado Increases Yields and Nitrogen Fixation. (1st March 2018) - da Silva Júnior, Elson B.; Favero, Vinício Oliosi; Xavier, Gustavo R.; Boddey, Robert M.; Zilli, Jerri E.
Abstract : Core Ideas: Cowpea cropping after soybean is increasing in the Cerrado region of Brazil and can benefit from BNF. Soybean bradyrhizobia can abundantly nodulate cowpea but are often inefficient. Inoculated elite cowpea Bradyrhizobium strains increased grain yields. Nitrogen fixation inputs were increased by inoculation with selected cowpea bradyrhizobia. Nitrogen‐15 natural abundance showed inoculation increased N2 fixation by over 25 kg N ha –1 crop –1 . Cowpea ( Vigna unguiculata Walp.) is increasingly planted as a second season crop after soybean [ Glycine max (L.) Merr.] in the Brazilian Cerrado region. Experiments were conducted at Sinop and Primavera do Leste in Mato Grosso State to investigate the impact of cowpea inoculation with recommended rhizobium strains on biological nitrogen fixation (BNF) and grain yield. Plants were either non‐inoculated, with or without 70 kg N fertilizer ha −, or inoculated with five rhizobium strains, separately or as a mixture. Nodulation and shoot dry matter (DM) were evaluated at 35 d after emergence (DAE). Dry matter and N accumulation were evaluated and BNF contributions quantified using 15 N natural abundance at 50 DAE. Nodule number and dry weight were high regardless of inoculation treatment. However, several of the inoculation treatments at Sinop and Primavera do Leste promoted significant increases in total N at 50 DAE. At both sites, the 15 N abundance results indicated that inoculation significantly increased BNF contributions from 36 to 64 kg ha − at Sinop and from 48 to 75 kg N ha − at Primavera. Grain yield was significantly increased from approximately 1200 to 1500 kg ha − by strains BR 3262 and INPA 03‐11B at the Primavera do Leste, and from approximately 850 to 1400 kg ha − by strain BR 3262 at Sinop. The results indicate inoculation of cowpea with elite rhizobium strains can increase BNF contributions and grain yields in the Brazilian Cerrado region, even when there are abundant populations of soybean rhizobium present in the soil.